Local Potential Development Model Based on Communal Intellectual Property in Serang District - Inge Dwisvimiar; Rully Syahrul Mucharom (Jurnal Cakrawala Hukum, 2024)
This article reviews Minister of Home Affairs Regulation Number 9 of 2014 concerning Guidelines for Development of Regional Featured Products, Law Number 28 of 2014 on Copyright, and Law Number 5 of 2017 on Advancement of Culture. The article aims to ascertain how Serang Regency's local and regional potential is distributed across its products and culture and to outline and identify a development model that Serang Regency's local and regional potential can apply to the region's intellectual property. The article employs a socio-legal research methodology along with a qualitative method—analysis and discussion around the allocation of local and regional. With an emphasis on Golok Seuat, Silat Bandrong, and Rudat, the analysis and discussion of local and regional potential distribution based on communal intellectual property, including products and culture, is highly varied. Golok Seuat is widely distributed and fairly even, but Rudat and Silat Bandrong are not uniformly distributed for various reasons. While Silat Bandrong and Rudat have been inventoried, secured, and published, the development approach employed in Golok Seuat is based on regional superior products with a core competency model with improved attractiveness and promotion.